n, n + 2, n + 4 - three consecutive even integers
the twice the sum of the second and third: 2[(n + 2) + (n + 4)]
twelve less than six times the first: 6n - 12
The equation:
2[(n + 2) + (n + 4)] = 6n - 12
2(n + 2 + n + 4) = 6n - 12
2(2n + 6) = 6n - 12 <em>use distributive property</em>
(2)(2n) + (2)(6) = 6n - 12
4n + 12 = 6n - 12 <em>subtract 12 from both sides</em>
4n = 6n - 24 <em>subtract 6n from both sides</em>
-2n = -24 <em>divide both sides by (-2)</em>
n = 12
n + 2 = 12 + 2 = 14
n + 4 = 12 + 4 = 16
<h3>Answer: 12, 14, 16</h3>
6/40 6.0/40.0 because it’s decimal and percentage wiser
Answer: 7,308
Step-by-step explanation: 28 X 9 = 252
252 X 29 = 7,308
when you simplify 2/4 it equals 1/2. Making them both equal the same.
2/3 when you double the numbers to make a bigger fraction you make 4/6.
2x2 = 4/ 3x3= /6 = 4/6
3/9 simplified is 1/3. Three goes into three one time, making the top one and three goes into 9 three times making the bottom 3.
When 9/12 is rounded down it is equivalent to 3/4